Cr(VI) Generation During Flaring of CO-Rich Off-Gas from Closed Ferrochromium Submerged Arc Furnaces - du Preez, S. P.; Beukes, J. P.; van Zyl, P. G. (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2015)
Ferrochromium (FeCr) is the only source of new Cr units used in stainless steel production, which is a vital modern day alloy, making FeCr equally important. Small amounts of Cr(VI) are unintentionally formed during several FeCr production steps. One such production step is the flaring of CO-rich off-gas from closed submerged arc furnaces (SAF), for which Cr(VI) formation is currently not quantified. In this study, the influence of flaring temperature, size of the particles passing through the flare, and retention time within the flame were investigated by simulating the process on laboratory scale with a vertical tube furnace. Multiple linear regression (MLR) analysis was conducted on the overall dataset obtained, which indicated that retention time had the greatest impact on pct Cr(VI) conversion, followed by particle size and temperature. The MLR analysis also yielded an optimum mathematical solution, which could be used to determine the overall impact of these parameters on pct Cr(VI) conversion. This equation was used to determine realistic and unrealistic worst-case scenario pct Cr(VI) conversions for actual FeCr SAFs, which yielded 2.7 × 10 −2 and 3.5 × 10 −1 pct, respectively. These values are significantly lower than the current unsubstantiated pct Cr(VI) conversion used in environmental impact assessments for FeCr smelters, i.e. , 0.8 to 1 pct.